The Impact Of Halal Investment On Commitment To Social Responsibility And Promoting Development - Hashem Osamah Yahya Mohammed; Ameen Al-Nahari; Baidar Mohammed Mohammed Hasan (Universal Publishers, 2026)
Indexed by ERA